The complaint handling procedure under the Malaysian dental act 1971 and dental regulations 1976: a comparative study with the United Kingdom and Hong Kong / Mohamad Asri Din, Lailihanim Mahmood, Md Alier Isa - Din, Mohamad Asri; Mahmood, Lailihanim; Isa, Md Alier (2012)
The Malaysian Dental Council (MDC) as the national regulatory body regulates dental professional in Malaysia with the mission to protect the public by ensuring the highest professional standards and ethics in the practice of dentistry through the administration of the Dental Act 1971 and Dental Regulations 1976. MDC investigates all complaints by the patients or other persons against any dental practitioner starting with the preliminary inquiry before a Preliminary Investigation Committee followed by the hearing at the Dental Council and eventually to the High Court in case swhere the complainants are not satisfied with the judgement made by the Council. The research adopts the qualitative approach, whereby a comparative study between the Malaysian provisions in the Malaysian Dental Act 1971 and Malaysian Dental Regulations 1976, and the laws in the UK Dentists Act 1984 and the Hong Kong Dentists Registration Ordinance 1997 is made. Specific observations are made on the areas of Pre-Dental Council hearing procedures, the process of hearing at the Council level and the subsequent actions and punishments after the hearings. Based on these findings, it is noted that there are not much differences in terms of what is being practised in Malaysia with those in the UK and Hong Kong. However there are areas of improvements that could be implemented in Malaysia based on the study. This is reflected in the chapter on recommendation section of this study. This research is hoped to benefit the Malaysian Dental Council in improving and speeding up their backlog of cases, give fairness to complainants as well as dental practitioners and also put forth some recommendations for the amendment of irrelevant provisions of the Dental Act 1971 and Dental Regulations 1971.